Working memory and referential communication—multimodal aspects of interaction between children with sensorineural hearing impairment and normal hearing peers - Sandgren, Olof; Hansson, Kristina; Sahlén, Birgitta (Frontiers in Psychology, 2015)
Whereas the language development of children with sensorineural hearing impairment (SNHI) has repeatedly been shown to differ from that of peers with normal hearing (NH), few studies have used an experimental approach to investigate the consequences on everyday communicative interaction. This mini review gives an overview of a range of studies on children with SNHI and NH exploring intra- and inter-individual cognitive and linguistic systems during communication. Over the last decade, our research group has studied the conversational strategies of Swedish speaking children and adolescents with SNHI and NH using referential communication, an experimental analogue to problem-solving in the classroom. We have established verbal and nonverbal control and validation mechanisms, related to working memory capacity (WMC) and phonological short term memory (PSTM). We present main findings and future directions relevant for the field of cognitive hearing science and for the clinical and school-based management of children and adolescents with SNHI.